Antimicrobial Susceptibility of Klebsiella pneumoniae and Escherichia coli with Extended-Spectrum β-lactamase associated Genes in Hospital Tengku Ampuan Afzan,Kuantan, Pahang - Yahya Mohsen, Saleh Mahdi; Hamzah, Hairul Aini; Mustafa Mahmoud, Mohammed Imad Al-Deen; Baharudin, Roesnita (Universiti Sains Malaysia, 2016)
Background: To assess antimicrobial susceptibility of extended-spectrum β-lactamase- (ESBL-) producing Klebsiella pneumoniae and Escherichia coli isolates from Hospital Tengku Ampuan Afzan (HTAA), as well as to identify ESBL genes. Methods: Non-duplicate K. pneumoniae and E. coli isolates were recovered from various clinical samples. Isolates were screened for antimicrobial resistance by disc diffusion method. Isolates resistant to oxyimino-cephalosporins were subjected to phenotypic ESBL production. Detection of resistance genes was then performed using primers specific for ESBL genes(bla CTX-M,bla SHV and bla TEM). Results: Piperacillin/tazobactam and carbapenems remained the active β-lactam antibioti against K. pneumoniae and E. coli. ESBLs were detected among 35.5%(39/110)of K. pneumoniae and 18.8%(28/149)of E. coli isolates. CTX-M β-lactamase was detected in 90% of all ESBL-positive isolates, whereas bla SHV and bla TEM genes were found among 56% and 52% of them, respectively. Twenty-eight percent(28%)of the total ESBL-positive isolates harboured the three ESBL genes, while 50% carried two of the tested ESBL genes. Conclusion ESBLs encoded by at least one ESBL genes are frequently isolated among K. pneumoniae and E. coli in HTAA. The significant proportion rate of the resistant determinants is alarming, thus monitoring their transmission and dissemination is essential to control it at an early phase.